A Practical Guide to Activities for Young Children - Hobart, Christine; Frankel, Jill. (Cheltenham : Stanley Thornes, 1995)
This is a guide to the management of the activities that should be available to young children from 0 to 7. Written by experienced professionals, this book covers all aspects of planning and organising experiences for young children.
Includes bibliographical references (p. 124-125).
Keywords: Child rearing; Children -- Recreation; Early childhood education -- Activity programs; Child Care